PEMANFAATAN RADIOISOTOP 32P UNTUK PENANDAAN (LABELLED COMPOUND) PADA NYAMUK Aedes aegypti - Darwin, Akhid; S., Lulus; Rahayu, Ali (Badan Penelitian dan Pengembangan Kesehatan, 2010)
An Ae. aegypti mosquitoes labelling with Radioisotop 32P was performed at various dose application. The research conducted by Insitute of Vector and Reservoir Control Research and Development, Salatiga in collaboration with The National of Atomic Agency that aimed to know the effective dose and radioactivity disposal of the Radioisotop 32 P. The research used several doses: 0,3 µCi (micro currie); 0,5 µCi; and 0,7 µCi of each 25 gr larvaefood for 50 larvae with dry and wet radiation then observed the effect of radiation against larvae stadium and mosquitoes. The result shows that at 0,5 pCi isotop 32P dose application, Ae. aegypti mosquitoe can survive with 333,3 cps (currie per second) residual radioactivity and detected in 75 cm distance. The Radioisotop 32P can be used as Ae. aegypti mosquitoes labelling/marking.